The autoantibody-mediated encephalitides: from clinical observations to molecular pathogenesis - Ramanathan, S; Al-Diwani, A; Waters, P; Irani, S (Springer, 2019)
The autoimmune encephalitis (AE) syndromes have been characterised by the detection of autoantibodies in serum and/or cerebrospinal fluid which target the extracellular domains of specific neuroglial antigens. The clinical syndromes have phenotypes which are often highly characteristic of their associated antigen-specific autoantibody. For example, the constellation of psychiatric features and the multi-faceted movement disorder observed in patients with NMDAR antibodies are highly distinctive, as are the faciobrachial dystonic seizures observed in close association with LGI1 antibodies. These typically tight correlations may be conferred by the presence of autoantibodies which can directly access and modulate their antigens in vivo. AE remains an under-recognised clinical syndrome but one where early and accurate detection is critical as prompt initiation of immunotherapy is closely associated with improved outcomes. In this review of a rapidly emerging field, we outline molecular observations with translational value. We focus on contemporary methodologies of autoantibody detection, the evolution and distinctive nature of the clinical phenotypes, generalisable therapeutic paradigms, and finally discuss the likely mechanisms of autoimmunity in these patients which may inform future precision therapies.